Design of highly active cobalt catalysts for CO2 hydrogenation via the tailoring of surface orientation of nanostructures. Issue 8 (27th March 2019) - Jimenez, Juan D.; Wen, Cun; Lauterbach, Jochen
Abstract : Catalyst design by tuning surface structures to suppress unreactive species in order to achieve higher reactivity for CO2 conversion. Abstract : The synthesis of nanomaterials with well-controlled morphologies and surface orientations has opened new avenues towards increasing catalytic performance and understanding of fundamental catalytic pathways. Here, we illustrate how tailoring surface orientations of Co3 O4 catalysts on the nanoscale results in control over catalytic performance via the preferential formation of active surface species during CO2 hydrogenation. This results in a significant increase in the methane yield on Co3 O4 nanorods, as opposed to conventional nanoparticle catalysts, where Co3 O4 nanorods inhibit the formation of formate spectator species via the preferential formation of bridged CO as an intermediate species. This design approach provides a new dimension for the development of next generation catalysts and opens new, more efficient strategies for the conversion of carbon dioxide into useful hydrocarbons.